The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1590/s1677-5538.ibju.2023.9904
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity extracorporeal shockwave therapy in the treatment of erectile dysfunction – a narrative review

Abstract: Objectives: To provide an overview of low-intensity extracorporeal shockwave therapy (LIEST) for erectile dysfunction (ED), pointing out which concepts are already consolidated and which paths we still need to advance. Materials and Methods: We performed a narrative review of the literature on the role of shockwave therapies in erectile dysfunction, selecting publications in PUBMED, including only relevant clinical trials, systematic reviews and meta-analyses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Dr. Vieiralves and collegues from Brazil, presented in page 428 ( 1 ) a nice review, the cover of the present edition, about the low-intensity extracorporeal shockwave therapy (LIEST) for erectile dysfunction (ED) and concluded that literature presents little scientific evidence but suggests good results with the use of LIEST for ED. Despite a real optimism since it is a treatment modality capable of acting on the pathophysiology of ED, we must remain cautious, until a lar- ger volume of higher quality studies allows us to establish which patient profile, type of energy and application protocol will achieve clinically satisfactory results.…”
mentioning
confidence: 99%
“…Dr. Vieiralves and collegues from Brazil, presented in page 428 ( 1 ) a nice review, the cover of the present edition, about the low-intensity extracorporeal shockwave therapy (LIEST) for erectile dysfunction (ED) and concluded that literature presents little scientific evidence but suggests good results with the use of LIEST for ED. Despite a real optimism since it is a treatment modality capable of acting on the pathophysiology of ED, we must remain cautious, until a lar- ger volume of higher quality studies allows us to establish which patient profile, type of energy and application protocol will achieve clinically satisfactory results.…”
mentioning
confidence: 99%